Assessment of the effectiveness of physiotherapy in children with cerebral palsy in the opinion of the parents - Łentek, Monika; Zdziarski, Krzysztof (Journal of Education, Health and Sport, 2022)
Many specialists have studied cerebral palsy. Currently, the most accurate definition is that proposed by Bax, who defines cerebral palsy as a disorder of posture and movement caused by damage to the brain. The factors that predispose to the development of this disorder include: pre-contraceptive, prenatal, perinatal and postnatal. Symptoms indicating the possibility of cerebral palsy can be observed already in the neonatal period, therefore it is important to follow pediatric visits, and in case of alarming symptoms, consult a neurologist. Early diagnosis of the disorder will allow the introduction of quick, individualized child physiotherapy, which may strengthen the child’s psychomotor development. Aim of the research: to assess the effectiveness of physiotherapy in children with cerebral palsy in the opinion of the parents. Material and methods: the proprietary questionnaire and two certified scales were used: Gross Motor Classification System to determine the degree of motor disorders and Manual Ability Classification System to check the degree of manual skills. Results: 67% of parents support the high effectiveness of physiotherapy. Therapeutic sessions most often take place 3-5 times a week (51%); moreover, 97% of children perform rehabilitation exercises at home. Conclusions: Physiotherapy is an effective form of exercise therapy for children with cerebral palsy. The most popular of the methods used in working with children is NDT-Bobath. The desirability of early diagnosis of cerebral palsy is associated with the possibility of quick therapeutic sessions, which translates into benefits in psychomotor development and significantly improves the quality of life.